Problems and Prospects of Formation of Digital Competence of Future Scientific and Pedagogical Workers of Higher Education Institutions Through Gamification: Opportunities Kahoot, Quizlet in the European Union - Holiuk, O.; Kruty, K.; Desnova, I.; Blashkova, O. M.; Korylchuk, N.; Блашкова, О. М. (Sciedu Press, 2022)
This article discussed the trends and features of the formation of digital competence of future teachers through virtual games such as Kahoot and Quizlet. The purpose of this article was to identify modern features of the use of virtual games in the educational process of future teachers in European Union. To achieved this goal, an analytical study was conducted on the use of Kahoot and Quizlet in education. A logical, historical, and comparative legal method was used to research prospects of formation of digital competence of future scientific and pedagogical workers of higher education institutions through gamification. Using a comparative legal method, a comparative analysis of the level of use of gamification tools. As a result, conclusions were made about a significant increase in the level of use of gamification tools in various types of educational activities of future research and teaching staff. It was determined that there are negative and positive effects of gamification. It is concluded that the use of gamification tools in various types of educational activities requires students to develop additional skills that are necessary in today's world. Active use of Kahoot, Quizlet in education helps to improve students' adaptive and social skills, quickly analyze their achievements and easily convey new information. Moreover, this format contains features before the usual learning format. Therefore, the problem of developing appropriate methods and skills of gamification in education was becoming urgent. As a result, it was determined that the topic of effective use of gamification tools in education is becoming increasingly important.
Keywords: education; virtual reality; digital competencies; information technologies; digitalization; virtual game